2021
DOI: 10.3389/fmicb.2021.576763
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soil Fungal Communities to Lime Application in Wheat Fields in the Pacific Northwest

Abstract: Liming is an effective agricultural practice and is broadly used to ameliorate soil acidification in agricultural ecosystems. Our understanding of the impacts of lime application on the soil fungal community is scarce. In this study, we explored the responses of fungal communities to liming at two locations with decreasing soil pH in Oregon in the Pacific Northwest using high-throughput sequencing (Illumina MiSeq). Our results revealed that the location and liming did not significantly affect soil fungal diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Similarly, fungal saprotrophs and fungal plant pathogens were negatively linked to calcium carbonate content while AMF were positively linked to it. Studies linking calcium carbonate to fungal functional groups at a large scale are virtually missing and further investigations could contribute to a better assessment of lime application impacts on fungal functional groups 59 . As the relationship between the addition of calcium carbonate and deacidification of soil pH is non-linear 60 , being able to relate both lime application and targeted pH correction to variations in fungal symbionts and fungal pathogens in soils may help to quantitatively assess the impacts of this agricultural practice on soil functioning, and contribute to better decisions on soil management.…”
Section: Single Drivers Of Functional Potentialmentioning
confidence: 99%
“…Similarly, fungal saprotrophs and fungal plant pathogens were negatively linked to calcium carbonate content while AMF were positively linked to it. Studies linking calcium carbonate to fungal functional groups at a large scale are virtually missing and further investigations could contribute to a better assessment of lime application impacts on fungal functional groups 59 . As the relationship between the addition of calcium carbonate and deacidification of soil pH is non-linear 60 , being able to relate both lime application and targeted pH correction to variations in fungal symbionts and fungal pathogens in soils may help to quantitatively assess the impacts of this agricultural practice on soil functioning, and contribute to better decisions on soil management.…”
Section: Single Drivers Of Functional Potentialmentioning
confidence: 99%
“…For the fungal families, weed soils were enriched with Chaetomiaceae , which is known to degrade recalcitrant plant material ( Habtewold et al, 2020 ), thereby releasing plant-derived cellulose that supports the growth of bacterial and fungal communities ( Eichorst and Kuske, 2012 ). Nectriaceae is a known soil-borne pathogenic family of fungi that is positively associated with certain plant traits (shoot and root biomass; Yin et al, 2021 ). Our results show that more harmful fungal taxa with known pathogenic traits were overrepresented in Ms. rhizosphere soil, including Nectriaceae and Pleosporaceae.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the taxonomic changes observed in endophytic communities were primarily due to PB2 inoculation, which redirected the community towards a higher abundance of Proteobacteria. Fungal diversity was slightly reduced in the rhizosphere of both cultivars upon inoculation with PB2, resulting in the promotion of saprophytic fungi, such as Peziza [56], some of which may also contribute to improved plant performance [57].…”
Section: Discussionmentioning
confidence: 99%